2001
DOI: 10.1258/0023677011911381
|View full text |Cite
|
Sign up to set email alerts
|

The impact of reduced frequency of cage changes on the health of mice housed in ventilated cages

Abstract: SummaryOur purpose in this investigation was to determ ine if we could reduce cage changing frequency without adversely affec ting the health of mice. We housed mice at three different cage changing frequencies: 7, 14, and 21 days, each at three different cage ventilat ion rates: 30, 60 and 100 air changes per hour (ACH), for a total of nine experimental conditions. For each condition, we evaluated the health of 12 breeding pairs and 12 breeding trios of C57BL = 6J mice for 7 months. Health was assessed by bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
84
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(89 citation statements)
references
References 14 publications
3
84
0
2
Order By: Relevance
“…However, it is also important to consider the optimal microclimate for the growing pups. ReebWhitaker et al 5 found that, although more pups survived, they had lower weaning body weights at 100 ACH than at 30 ACH, which might indicate a too cold environment for them. These pups did not have access to nesting material which is important for modulating the microclimate and likely reduces the cooling effect on them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also important to consider the optimal microclimate for the growing pups. ReebWhitaker et al 5 found that, although more pups survived, they had lower weaning body weights at 100 ACH than at 30 ACH, which might indicate a too cold environment for them. These pups did not have access to nesting material which is important for modulating the microclimate and likely reduces the cooling effect on them.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have assessed the levels of CO 2 and NH 3 , relative humidity (RH) and temperature in the cages with different cage changing intervals, air changes per hour (ACH) and population densities in the cages. [2][3][4][5][6][7] However, the effect on animals housed in this type of cage environment has just started to be evaluated in recent years. Studies have shown that rodents in general prefer non-ventilated cages to ventilated ones, that they prefer cages with the lowest number of ACH, and larger cages to smaller ones.…”
mentioning
confidence: 99%
“…In the long term, frequent cleaning causes chronic stress in mice; more frequent cleaning reduces weight gain (Beynen & Vantintelen 1990) and increases pupmortality (Reeb-Whitaker et al 2001, Peters et al 2002. If lower cleaning rates benefit rodents, their application would also be more economical for animal units, leading to less waste and reduced workloads for technicians.…”
mentioning
confidence: 99%
“…Even when not clinically recognized, elevated ammonia may significantly affect drug studies and liver function [11] and may contribute to elevated corticosterone values [9]. Excessive ammonia accumulation emerges with reduced cage changing frequency [10], in the presence of inadequate ventilation [9,12], under conditions of higher humidity, and with increased animal densities or nitrogen load [13]. Certain bedding types accentuate ammonia production [14,15] while excessive ventilation rates may affect breeding success (Wimsatt, unpublished data).…”
Section: Discussionmentioning
confidence: 99%